Supporting personal security using participatory sensing. (12th December 2014) - Carreño, Pablo; Gutierrez, Francisco J.; Ochoa, Sergio F.; Fortino, Giancarlo; Xiang, Yang; Pathan, Mukaddim; Wei, Guiyi; Fortino, Giancarlo
Summary Personal security is an open problem in large cities. After several attempts to reduce violence and crime, there seems to be an agreement that preventive actions are the best way to address this problem. Trying to help deal with that challenge, this paper proposes a mobile collaborative application, named Personal Guardian, which is used by civilians while walking in urban areas. The application is focused on crime prevention and it implements participatory sensing to help people be aware of the risks that appear to exist in a certain place at a certain time. Based on that information, citizens can take appropriate and on‐time preventive actions. The system is supported by a human‐centric wireless sensor network, and it is complementary to the security solutions already used by public and private organizations. The system architecture and its main components are described, and the main requirements and design decisions are also discussed. A preliminary evaluation of the solution was conducted to determine its strengths and weaknesses in terms of quality of service. The obtained results indicate that the information feeding process is more relevant for end‐users than the unattended delivery of awareness information about their personal security. In addition, this former capability does not require to be adjusted to the end‐users' context. Copyright © 2014 John Wiley & Sons, Ltd.